Developing & testing a web tool to improve consultation participation and outcomes in older patients: Presenter(s): Melanie de Looper, ASCoR, University of Amsterdam, Netherlands. (April 2023) - Smets, Ellen; Schouten, Barbara; Bolle, Sifra; Belgers, Eric; Eddes, Eric Hans; Leijtens, Jeroen; van Weert, Julia
Abstract : Older cancer patients may search for health information online to prepare for their consultations. However, seeking information online can have negative effects, for instance increased anxiety due to finding incorrect or unclear information. Therefore, an online health information tool aimed at older cancer patients was systematically developed, implemented and evaluated, providing information that complements the consultation with healthcare providers. For the development and evaluation of the Patient Navigator, the four phases of the MRC framework were used. In the first and second phase the Patient Navigator was developed and pilot tested. During the third phase the Patient Navigator was implemented in four Dutch hospitals. In the last phase, a pilot RCT was conducted to evaluate the Patient Navigator in terms of usage (observational tracking data), user experience (satisfaction, involvement, cognitive load, active control, perceived relevance), patient participation (observational data during consultation), and patient outcomes related to the consultation (anxiety, satisfaction, and information recall). Recently diagnosed colorectal cancer patients (N = 45) were randomly assigned to the control condition (usual care) or the experimental condition (usual care + Patient Navigator). The Patient Navigator was well used and evaluated positively. Patients who received the Patient Navigator contributed less during the consultation by using less words than patients in the control condition and experienced less anxiety two days after the consultation than patients in the control condition. Since the Patient Navigator was evaluated positively and decreased anxiety after the consultation, this tool is potentially a valuable addition to the consultation for patients. Usage of the Patient Navigator resulted in patients using less words during consultations, without impairing patients' satisfaction, possibly because information needs might be fulfilled by usage of the Patient Navigator. This could create the possibility to personalize communication during consultations and respond to other patient needs.